Reinforcing Stromal Cell Spheroid Through Red‐Light Preconditioning for Advanced Vascularization - Yu‐Jin Kim; Hyeok Kim; Dong‐Hyun Lee; Yeong Hwan Kim; Jae‐Hyun Park; Woo‐Sup Sim; Jin‐Ju Kim; Kiwon Ban; Soong Ho Um; Hyun Ji Park; Michael E. Davis; Hun‐Jun Park; et al. (Advanced Science)
Abstract Despite the promising potential of stromal cell therapy in treating myocardial infarction (MI), its effectiveness is limited by poor cell retention and engraftment in ischemic environments. This study introduces a novel strategy that combines the preconditioning of human adipose‐derived stromal cells (hADSCs) using OLED‐based photobiomodulation (OPBM) and culturing these cells into 3D spheroids. The preconditioned 3D spheroids (APCS group) exhibit significantly enhanced angiogenic, arterialized, and tissue remodeling capabilities compared with those of traditional 2D cultures and non‐preconditioned spheroids. In vivo transplantation of these spheroids into the border zone of infarcted area significantly improve cardiac function and reduce adverse remodeling by enhancing anti‐fibrosis and angiogenesis including arterialization. The combined strategy with OPBM preconditioning and 3D spheroid culture system can enhance therapeutic potential of hADSCs with multiple paracrine effects for cardiac repair. This novel approach provides next generation of cell therapeutics to overcome the limitation of adult stromal cell therapy in patients with post‐MI heart failure.